2016
DOI: 10.1016/j.ejmech.2016.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Novel c-Met inhibitory olive secoiridoid semisynthetic analogs for the control of invasive breast cancer

Abstract: Dysregulated receptor tyrosine kinase c-Met and its ligand HGF is valid and attractive molecular target for therapeutic blockade in cancer. Inspired by the chemical structure of the naturally occurring olive secoiridoid (-)-oleocanthal (1) and its documented anticancer activity against c-Met-dependent malignancies, a previous study reported tyrosol sinapate (4) as a c-Met inhibitor hit. This study reports additional semisynthetic optimization and SAR of 4 to improve its selective activity against c-Met-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Earlier studies indicated that (−)-oleocanthal is a potential inhibitor of the hepatocyte growth factor receptor (c-Met) pathway in breast cancer cells (Akl et al, 2014; Elnagar et al, 2011; Mohyeldin et al, 2016b). The antiproliferative effects of (−)-oleocanthal are mediated by inhibiting multiple c-Met downstream signaling molecules including protein kinase B (Akt), mitogen-activated protein kinase (MAPK), signal transducers and activators of transcription-3 (STAT-3), and mammalian target of rapamycin (mTOR) in multiple cancer cells (Akl et al, 2014; Fogli et al, 2016; Khanal et al, 2011; Khanfar et al, 2015; Pei et al, 2016; Scotece et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies indicated that (−)-oleocanthal is a potential inhibitor of the hepatocyte growth factor receptor (c-Met) pathway in breast cancer cells (Akl et al, 2014; Elnagar et al, 2011; Mohyeldin et al, 2016b). The antiproliferative effects of (−)-oleocanthal are mediated by inhibiting multiple c-Met downstream signaling molecules including protein kinase B (Akt), mitogen-activated protein kinase (MAPK), signal transducers and activators of transcription-3 (STAT-3), and mammalian target of rapamycin (mTOR) in multiple cancer cells (Akl et al, 2014; Fogli et al, 2016; Khanal et al, 2011; Khanfar et al, 2015; Pei et al, 2016; Scotece et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In silico binding studies were performed using Schrödinger molecular modeling software (v9, Schrodinger, New York, NY, USA), as previously described [ 56 ]. The calcium site domain of each of the BK channel crystal structure PDB codes 3NAF and 3MT5, resolution ≥3 Å, was prepared using the protein preparation wizard, applying PROPKA (Jensen Research Group, Denmark) to add hydrogens, assign bond orders, and optimize hydrogen bonding networks.…”
Section: Methodsmentioning
confidence: 99%
“…The LigPrep wizard using OPLS force field was chosen to prepare the 3D-dimensional structure of each analog, undergo geometric optimization, search for different conformers, and calculate partial atomic charges. Docking of penitrems was then conducted using the Glide 5.8 module (Glide, 2012, Schrodinger, New York, NY, USA) in extra-precision (XP) mode or in standard-precision mode (SP) [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the case of ZINC03871891 bound to the active conformation, it did not form hydrogen bond with any residues in the hinge region, a typical characteristic of all kinase inhibitors targeting the ATP-binding site [25,35]. Instead, hydrophobic interactions were found with M1160, suggesting a lower binding affinity with an IC 50 of 18.76 nM.…”
Section: Docked Structures Of the Hit Compoundsmentioning
confidence: 96%